One-dimension-based spatially ordered architectures for solar energy conversion. (9th April 2015) - Liu, Siqi; Tang, Zi-Rong; Sun, Yugang; Colmenares, Juan Carlos; Xu, Yi-Jun
Abstract : The current status, future developments, and challenges of one-dimension-based spatially ordered architectures in solar energy conversion are discussed and elucidated. Abstract : The severe consequences of fossil fuel consumption have resulted in a need for alternative sustainable sources of energy. Conversion and storage of solar energy via a renewable method, such as photocatalysis, holds great promise as such an alternative. One-dimensional (1D) nanostructures have gained attention in solar energy conversion because they have a long axis to absorb incident sunlight yet a short radial distance for separation of photogenerated charge carriers. In particular, well-ordered spatially high dimensional architectures based on 1D nanostructures with well-defined facets or anisotropic shapes offer an exciting opportunity for bridging the gap between 1D nanostructures and the micro and macro world, providing a platform for integration of nanostructures on a larger and more manageable scale into high-performance solar energy conversion applications. In this review, we focus on the progress of photocatalytic solar energy conversion over controlled one-dimension-based spatially ordered architecture hybrids. Assembly and classification of these novel architectures are summarized, and we discuss the opportunity and future direction of integration of 1D materials into high-dimensional, spatially organized architectures, with a perspective toward improved collective performance in various artificial photoredox applications.